2016
DOI: 10.3389/fpsyg.2016.01884
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and Identifiability of Model Parameters in Human Nociceptive Processing Using Yes-No Detection Responses to Electrocutaneous Stimulation

Abstract: Healthy or pathological states of nociceptive subsystems determine different stimulus-response relations measured from quantitative sensory testing. In turn, stimulus-response measurements may be used to assess these states. In a recently developed computational model, six model parameters characterize activation of nerve endings and spinal neurons. However, both model nonlinearity and limited information in yes-no detection responses to electrocutaneous stimuli challenge to estimate model parameters. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(77 reference statements)
0
3
0
Order By: Relevance
“…We also analyzed structural model identifiability in order to study whether model parameters can be determined uniquely, by performing a profile likelihood analysis ( Yang et al, 2016 ; Raue et al, 2009 ) on the parameters γ and α ( Supplementary Text ). We found that the compound decay parameter γ is structurally identifiable ( Supplementary Figure S8 ), but the ion leakage rate α is not ( Supplementary Figure S9 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also analyzed structural model identifiability in order to study whether model parameters can be determined uniquely, by performing a profile likelihood analysis ( Yang et al, 2016 ; Raue et al, 2009 ) on the parameters γ and α ( Supplementary Text ). We found that the compound decay parameter γ is structurally identifiable ( Supplementary Figure S8 ), but the ion leakage rate α is not ( Supplementary Figure S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a PL approach one calculates a confidence interval, yet it also helps to identify parameters that are structurally non-identifiable ( Raue et al, 2009 ; Yang et al, 2016 ). The confidence interval for a parameter is determined by computing the dependence of the maximum likelihood (i.e., the two-fold logL, or NPL ) on the parameter that is being profiled (i.e., fixed at different values).…”
Section: Methodsmentioning
confidence: 99%
“…This was the motivation for the test developed by Logvinenko et al (2012) and it is a frequent concern in empirical studies that require the collection of large amounts of data across several sessions, where the observers' sensory state can vary across sessions (for empirical evidence to this effect see, e.g., García-Pérez, 2010;Leek, Hanna, & Marshall, 1991;von Dincklage, Olbrich, Baars, & Rehberg, 2013). A formal test is surely more dependable than judging by eye whether the shape described by data from different sessions look alike (e.g., Hutsell & Jacobs, 2013;Oliveira & Machado, 2008;Yang, Meijer, Buitenweg, & van Gils, 2016). In this type of application, each observer's data on each experimental condition are analyzed separately with I standing for the number of sessions at which data had been collected.…”
Section: Illustrative Applicationsmentioning
confidence: 99%